2009
DOI: 10.3322/caac.20014
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Aspiration Cytology: Current Status

Abstract: In the adult population, thyroid nodules are common and are increasingly detected by ultrasound examination or other scanning techniques. Depending on their size and ultrasonographic features, these nodules may require further investigation, including tissue diagnosis. Fine-needle aspiration (FNA) has become the predominant method to obtain tissue for microscopic analysis. In October 2007, the National Cancer Institute sponsored a conference to review the state of the science for the use of FNA in the manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
118
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 118 publications
8
118
0
9
Order By: Relevance
“…Thus, starting FNA using a thinner needle is recommended and thicker needles should generally be reserved for draining viscous colloid cysts. Generally, two to five passes seem reasonable to ensure an adequate sample (2,(35)(36)(37). Our results show that the incidence of hemorrhagic complications increased with an increase in the number of passes.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Thus, starting FNA using a thinner needle is recommended and thicker needles should generally be reserved for draining viscous colloid cysts. Generally, two to five passes seem reasonable to ensure an adequate sample (2,(35)(36)(37). Our results show that the incidence of hemorrhagic complications increased with an increase in the number of passes.…”
Section: Discussionsupporting
confidence: 54%
“…Our results show that the incidence of hemorrhagic complications increased with an increase in the number of passes. In previous studies, there were no statistically significant differences between the capillary sampling technique and FNA with suction with regard to diagnostic accuracy (37)(38)(39)(40). In our study, the hemorrhage complication rate was not significantly different between the two techniques.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…7 The major limitations of FNAB procedures are linked to inadequate and indeterminate specimens and, in that sense, are also linked respectively to the nondiagnostic or follicular lesions categories. 8,9 Thus, a clinical need emerges for the characterization of aspirates with suspicious features but with unsatisfactory cellularity, to allow accurate distinction of benign from malignant forms of follicular lesions.Several somatic mutations have been identified in thyroid cancer, stimulating the search for genetic alterations in FNAB that could increase the diagnostic accuracy of traditional cytology. Numerous studies have demonstrated that identification of specific mutations in cytological specimens can assist in the diagnosis by FNAB and in the clinical decision to excise the nodule and to intensify the follow-up.…”
mentioning
confidence: 99%
“…7 The major limitations of FNAB procedures are linked to inadequate and indeterminate specimens and, in that sense, are also linked respectively to the nondiagnostic or follicular lesions categories. 8,9 Thus, a clinical need emerges for the characterization of aspirates with suspicious features but with unsatisfactory cellularity, to allow accurate distinction of benign from malignant forms of follicular lesions.…”
mentioning
confidence: 99%